Electronic coherences and vibrational wave-packets in single molecules studied with femtosecond phase-controlled spectroscopy - Hildner, Richard (2011)
Employing femtosecond pulse-shaping techniques we investigate ultrafast, coherent and incoherent dynamics in single molecules at room temperature. In first experiments single molecules are excited into their purely electronic 0–0 transition by phase-locked double-pulse sequences with pulse durations of 75 fs and 20 nm spectral band width. Their femtosecond kinetics can then be understood in terms of a 2-level system and modelled with the optical Bloch equations. We find that we observe the coherence decay in single molecules, and the purely electronic dephasing times can be retrieved directly in the time domain. In addition, the Rabi-frequencies and thus the transition dipole moments of single molecules are determined from these data. Upon excitation of single molecules into a vibrational level of the electronically excited state also incoherent intra-molecular vibrational relaxation is recorded. Increasing the spectral band width of the excitation pulses to up to 120 nm (resulting in a transform-limited pulse width of 15 fs) coherent superpositions of excited state vibrational modes, i.e. vibrational wave packets, are excited. The wave-packet oscillations in the excited state potential energy surface are followed in time by a phase-controlled pump–probe scheme, which permits to record wave packet interference, and to determine the energies of vibrational modes and their coupling strengths to the electronic transition.